2022
DOI: 10.3389/fonc.2022.937166
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors and sensitization of cancer cells to radiation therapy

Abstract: This review article outlines six molecular pathways that confer resistance of cancer cells to ionizing radiation, and describes how proton pump inhibitors (PPIs) may be used to overcome radioresistance induced by alteration of one or more of these signaling pathways. The inflammatory, adaptive, hypoxia, DNA damage repair, cell adhesion, and developmental pathways have all been linked to the resistance of cancer cells to ionizing radiation. Here we describe the molecular link between alteration of these pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 108 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Examples of drugs that are successfully repurposed for oncologic indications include thalidomide (Contergan), a drug originally developed for the treatment of morning sickness and is now marketed for the treatment of multiple myeloma (marketed under the brand name Thalomid). Recently, we have taken the initiative to reformulate and repurpose the antacid drug Esomeprazole (Nexium) for the treatment of radiation dermatitis ( 23 , 24 ). Currently, this study is in phase II clinical trial for the new indication in patients with head and neck cancer (NCT04865731).…”
Section: Emerging Computational Approachesmentioning
confidence: 99%
“…Examples of drugs that are successfully repurposed for oncologic indications include thalidomide (Contergan), a drug originally developed for the treatment of morning sickness and is now marketed for the treatment of multiple myeloma (marketed under the brand name Thalomid). Recently, we have taken the initiative to reformulate and repurpose the antacid drug Esomeprazole (Nexium) for the treatment of radiation dermatitis ( 23 , 24 ). Currently, this study is in phase II clinical trial for the new indication in patients with head and neck cancer (NCT04865731).…”
Section: Emerging Computational Approachesmentioning
confidence: 99%
“…However, in the treatment of esophageal squamous cell carcinoma, PPIs may enhance the effect of 5-FU [20]. PPIs can also amplify the effects of radiation therapy by reducing the acidity of tumor cells-a phenomenon known as radio-sensitization-which has shown promise in preclinical studies [21].…”
Section: Interaction Of Ppis and Cancer Treatmentmentioning
confidence: 99%
“…To address acidity in TME, several researchers have reported that proton pump inhibitors may slow the growth of hepatoblastoma and oesophageal adenocarcinoma [88][89][90]. Proton pump inhibitors, such as omeprazole, esomeprazole, rabeprazole, pantoprazole, or lansoprazole, signifcantly slow the growth and development of neoplasms in individuals with Barrett's oesophagus [91].…”
Section: Targeting the Acidic Tmementioning
confidence: 99%